The ANQueSt (Asian Nurse Quality of Life Study) to compare quality of life and identify related variables: study protocol for a cross-sectional design - Makabe, Sachiko; Kowitlawakul, Yanika; Nurumal, Mohd. Said; Takagai, Junko; Wichaikhum, Orn-Anong; Wangmo, Neyzang; Foon, Yap Suk; Kunaviktikul, Wipada; Komatsu, Junko; Shirakawa, Hideko; Kimura, Yutaka; Asanuma, Yoshihiro (OMICS International, 2017)
Background: Hospital-based nurses’ quality of life is affected by stress coping ability, job satisfaction, job stress, and social support. These relationships appear to be identical, even among different countries. Nevertheless, dynamic comparisons of quality of life in Asia are very limited. The Asian Nurse Quality of Life Study was designed to compare nurses’ quality of life across Asian countries and identify variables that are related to quality of life. Research design: A cross-sectional questionnaire survey design. Subject: Hospital based nurses are recruited from Japan, Singapore, Malaysia, Thailand, and Bhutan (Five Asian countries). The inclusion criteria for the research are: 1) being from an Asian country, 2) working at a teaching hospital, and 3) obtaining the nursing director’s agreement. Co-researchers from each country independently select particular research fields. Method: A cross-sectional survey is conducted across five Asian countries (Japan, Singapore, Malaysia, Thailand, and Bhutan). Quality of life (WHOQOL-BREF), job stress (National Institute of Occupational Safety and Health questionnaire), and demographic data are assessed. Quality of life is directly compared among the countries. Stepwise multivariate linear regression analysis is performed to identify variables related to quality of life. Survey duration: Survey duration is between October 2013 and August 2014.